Exploring the bacteriophage in Malaysia: an overview of applications and challenges - Nur Nashyiroh Izayati Mastor; Mohammad Zahirul Hoque; Vijay Kumar Subbiah (Penerbit UMS, 2025)
Antibiotic resistance is a worldwide concern as more drugs are losing efficacy and fewer candidates are being developed in the pipeline. As a result, there is growing attention towards alternative applications of microbial control, and bacteriophages have come to the forefront of research. However, there is limited data and experimental studies in Malaysia. The well-documented use of these viruses to overcome the problem of antimicrobial resistance and multi-drug resistance is still scarce in the country and warrants exploration. Here, we discuss the potential of bacteriophage applications in healthcare, animal husbandry, aquaculture and agriculture in Malaysia. The challenges faced in doing so and reception among the country’s researchers, clinicians and healthcare authorities are also discussed. Although the use of bacteriophages in this capacity is just beginning to unfold, it is hoped that there will be a shift in perception towards a positive reception, especially with the looming threat of antibiotic resistance.